Friday

December 19, 2014

December 19, 2014

Posted by **Jennifer** on Sunday, February 5, 2012 at 2:30pm.

In the figure below, PQ=RS. Prove PR=QS.

____________________

P Q R S

- Geometry -
**Anonymous**, Sunday, February 5, 2012 at 6:20pmPR+RS = PS

PQ+QS = PS

so,

PR+RS = PQ+QS

but, PQ=RS, so

PR + PQ = PQ + QS

so,

PR = QS

**Answer this Question**

**Related Questions**

Geometry - I don't know how to do this proof It is set up on a T chart In the ...

geometry - Construction: The midpoint of a line segment can be constructed. ...

Geometry - Given: ray AD bisects <BAC <DAC=3x, and <BAD=5x-24 Prove: x=...

Geometry HELP - Using coordinate geometry to prove that the diagonals of a ...

geometry - ughh i need help i dnt like proofs we'll here it the instructions ...

Math- Geometry Proofs - What are some ways to prove that a triange is isoscles? ...

geometry - 1)given-AB=CD,CD=EF prove-AB-EF (in 5 steps that show why it is ...

geometry - in the digram below,prove that trianglel lmn is similar to trangle ...

geometry - Write a two-column proof. Given: 7y = 8x – 14; y = 6 Prove: x = 7

geometry - complete the two-column proof given: x/6+2=15 prove: x=78